The Effect of Financial Behavior and Income Level on Investment Decision in Digital Era - Wilson; Frenky Situmorang; Putri Wahyuni (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2023)
This study aims to determine whether financial behavior and income level have a significant effect on investment decisions of STIE Eka Prasetya permanent lecturers. This study uses quantitative data method and the data source is primary data. The population in this study are all permanent lecturers who taught at STIE Eka Prasetya, totaling 33 permanent lecturers. The sample in this study includes all permanent lecturers teaching at STIE Eka Prasetya, using a saturated sampling method. Data analysis and testing consist of validity test, reliability test, descriptive statistics, the classical assumption test, multiple regression analysis, partial hypothesis testing (T test), simultaneous hypothesis testing (F test), and coefficient of determination test (R²). The results of this study indicate that financial behavior has a significant effect on investment decisions with a calculated T-count of 2.113 > T-table of 2.039. Income Level does not have a significant effect on investment decisions with a calculated T-count of 0.821 < T-table of 2.039. Financial behavior and income level have a significant effect on investment decisions with a calculated F-count of 4.569 > F-table of 3.32 and a regression coefficient value of 23.3%.